Comparison of landing biomechanics between male and female professional dancers - Orishimo, K. F.; Kremenic, I. J.; Pappas, E.; Hagins, M.; Liederbach, M. (The American Journal of Sports Medicine, 2009)
The incidence of anterior cruciate ligament injuries among dancers is much lower than that among team sport athletes and no clear gender disparity has been reported in the dance population. Although numerous studies have observed differences in lower extremity landing biomechanics between male and female athletes, there is currently little research examining the landing biomechanics of male and female dancers. Comparing landing biomechanics within this population may help explain the lower overall anterior cruciate ligament injury rates and the lack of gender disparity.